A subplacenta do preá Galea spixii Wagler, 1831 - Bezerra, Ferdinando Vinícius Fernandes (Universidade Federal Rural do Semi-Árido, 2014)
The subplacenta is considered an ideal model for comparative studies of trophoblastic processes in humans. Thus, the aim of this study was made a morphological description of the development of the Spix s yellow-toothed cavy. To do this, 12 females were distributed in three groups in a proportion of 1 male to 4 females, kept in pickets of 5m2. Thereafter, vaginal cytology examinations were made daily, to verify if the females were copulated and to separate them from the other females. Then, the collection of subplacentas was made in the 15, 23, 30, 45, 53 and 55 days of gestation, by slaughtering the pregnant females using a specific anesthesic protocol. The samples were processed to standard histological techniques, cytochemistry and immunohistochemistry, and to transmission electronic microscopy. In the 15th day of gestation, the subplacenta was formed by a single cytotrophoblastic layer surrounded by a vacuolized syncytium with maternal lacunae which presented invasive characteristic in the portions apart of the cytotrophoblastic layer. In the 23th day of gestation, the subplacenta did not presented a well-defined shape, however, it was organized in lobules composed of predominantly of cytotrophoblast e its syncytium was related to the regions where maternal lacunae previously appeared. In the 30th day of gestation, the subplacenta appeared as a compact organ with a well-defined shape and with an evident mesenchymal capilarization; the lobules was composed by syncytiotrophoblast in the centre, and by a mesenchyme surrounded by cytotrophoblast. From the 45th day of gestation, the degeneration of the subplacental tissue was evident and the syncytiotrophoblast was more abundant than the cytotrophoblast; moreover, the syncytium was markedly vacuolized and presented signs of cellular death. Near to gestation term (53-54thday), the subplacenta was in an advanced degeneration stage, with evident signs of cellular death and reduction of subplacental tissue. The presence of fetal circulation was characteristic from the 23th day of gestation, evidenced by the positive reaction to vimentin; positive reaction to cytokeratin was observed during entire gestation. The proliferative activity of the subplacenta was assessed by PCNA and AgNOR procedures, and demonstrated to be higher in the beginning of the gestational period, decreasing progressively during the gestation. Ultrastructurally, the subplacenta presented cellular and syncytial trophoblastic characteristics. The development of the Spix s yellow-toothed cavy subplacenta starts around the 15th day of gestation, reaching maximum development in the 30th day and becomes necrotic in the end of gestation. Moreover, it presented an organization and structure similar to the subplacenta of other cavidae
The subplacenta of preá Galea spixii Wagler, 1831
Keywords: Cytotrophoblast; Development; Syncytiotrophoblast; Subplacenta; Citotrofoblasto; Desenvolvimento; Sinciciotrofoblasto; Subplacenta; CIENCIAS AGRARIAS::MEDICINA VETERINARIA